Convergence Analysis of Spectral Methods for Integro-Differential Equations with Vanishing Proportional Delays (Journal of Computational Mathematics, 2018)
We describe the application of the spectral method to delay integro-differential equations with proportional delays. It is shown that the resulting numerical solutions exhibit the spectral convergence order. Extensions to equations with more general (nonlinear) vanishing delays are also discussed.